2022
DOI: 10.1039/d1ra07599c
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the competition between antioxidant activities and pro-oxidant risks of rosmarinic acid

Abstract: Direct and indirect antioxidant activities of rosmarinic acid (RA) based on HOO˙/CH3OO˙ radical scavenging and Fe(iii)/Fe(ii) ion chelation were theoretically studied using density functional theory at the M05-2X/6-311++G(2df,2p) level of theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 95 publications
1
30
0
Order By: Relevance
“…Meanwhile, the ones in the bi-dentate complexes range from 2.11 to 2.56 Å and from 2.15 to 2.54 Å, respectively. As reported by previous works, the interaction distances in Fe(III) complexes are shorter than those in Fe(II) ones [24][25][26][27]. Cartesian coordinates and the thermochemistry data of all the Fe-Leu complexes are displayed in electronic supplementary material, table SI2.…”
Section: Fe Ions Chelationmentioning
confidence: 71%
See 2 more Smart Citations
“…Meanwhile, the ones in the bi-dentate complexes range from 2.11 to 2.56 Å and from 2.15 to 2.54 Å, respectively. As reported by previous works, the interaction distances in Fe(III) complexes are shorter than those in Fe(II) ones [24][25][26][27]. Cartesian coordinates and the thermochemistry data of all the Fe-Leu complexes are displayed in electronic supplementary material, table SI2.…”
Section: Fe Ions Chelationmentioning
confidence: 71%
“…The pro-oxidant risks of l -leucine are evaluated via the reduction reactions of Fe(III)-to-Fe(II)-Leu complexes and Cu(II)-to-Cu(I)-Leu complexes that may promote the production of reactive HO· radical by Fenton reactions [ 25 , 26 , 32 ]. Thermodynamic and kinetic data of the reduction reactions by two reducing agents, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 The influence of the aqueous media was mimicked by combining the implicit solvation model based on density (SMD) [34][35][36] and the polarizable continuum model (PCM), which several works have widely used in the literature. 37,38 ] + were employed as a recommendation by previous works. [38][39][40][41][42] The high-spin states of hydrated Fe(II) and Fe(III) ions in this study were equal to 5 and 6, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have confirmed that RA has strong antioxidant properties [ 7 ]. Due to the current consumer concerns about the safety of synthetic preservatives, plant extracts rich in polyphenols such as RA are increasingly being used to extend the shelf life of food and cosmetics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%